CONTINUOUS PERFORMANCE MANAGEMENT: MOVING BEYOND THE ANNUAL REVIEW - Amalia Natasya; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
This paper examines the transformative impact of implementing a structured real-time feedback system within organizations, moving beyond traditional annual review cycles. Quantitative data from a two-year study reveals that normalizing immediate, project-based feedback led to a 50% increase in the specificity and actionability of feedback provided. This shift correlated with significant performance improvements, including a 15-20% rise in client-facing metrics like customer satisfaction and a 22-point increase in employee engagement scores related to developmental growth. The analysis explores the neurocognitive advantage of immediate feedback, where the proximity to events enhances learning and retention, thereby systematically dismantling the